Results of Combined Pathogenetic Therapy in Netherton Syndrome: Clinical Case - Nikolay N. Murashkin; Leonid A. Opryatin; Anna S. Bridan-Rostovskaya; Ekaterina S. Pavlova; Roman A. Ivanov; Karine O. Avetisyan; Kirill A. Kulikov (Вопросы современной педиатрии, 2023)
Background. Netherton syndrome is a severe autosomal recessive disease based not only on genetically determined keratinization disorders, but also on immune system dysregulation.Clinical case description. Boy K., 9 years old, diagnosed with severe atopic dermatitis and revealed Netherton syndrome during examinations. The dupilumab was administered due to the presence of severe polysensitization and clinical signs of allergic process. Wave-like course of the disease was observed during this therapy. Patient had acute exacerbation — generalized pustular rash — at the 7th month of treatment. The therapy with secukinumab was initiated according to the foreign literature on pathogenetic treatment of Netherton syndrome with interleukin (IL) 17 inhibitor. It has shown positive dynamics. Currently patient is administered with the combined therapy of IL-17 and IL-4/13 inhibitors with significant positive effect.Conclusion. Genetically engineered biologic drugs targeting both the Th17 and Th2 have shown their efficacy in Netherton syndrome management.